Critical factors influencing wind power industry: A diamond model based study of India - Muhammad Irfan; Zhen-Yu Zhao; Munir Ahmad; Marie Claire Mukeshimana (Energy Reports, 2019)
The energy needs of India have increased many folds in recent years due to industrialization and ever-increasing population. Wind energy offers excellent opportunities in fulfilling the energy needs of the country. Being renewable, it has enormous resource potential. Since the last decade, the wind energy sector has progressed very quickly. India ranks 4th in the world in terms of installed wind capacity. The cumulative installed capacity has reached 35,288 MW, grabbing 6% global share. Meanwhile, various factors are affecting the development of the wind power industry. This paper aims to identify and analyze the critical factors that are significantly affecting the development and competitiveness of the Indian wind industry. For this purpose, we have adopted the Diamond model approach. After careful analysis, we have found that these factors are: demand condition, factor condition, chance, related and support industry, firm strategy, structure, rivalry, and government. All the factors identified in this model are influencing the wind industry's competitiveness from a different angle. Thus, these factors should be strengthened for the long-term development of the wind industry. Research findings reveal the present status, challenges, and future projections of the wind power industry. Essential policy recommendations have been offered for the sustainable development of this sector. Government and stakeholders can take benefit from this research by understanding the dynamic relationship among all the factors influencing the development of the wind power industry and make procurement strategies accordingly.
Keywords: 330; Diamond model; Grid construction; India; Policies; Wind energy; Wind turbine